Aortic root size and prevalence of aortic regurgitation in elite strength trained athletes - Babaee Bigi, M. A.; Aslani, A. (The American Journal of Cardiology, 2007)
Athletes involved in mainly static or isometric exercise (e.g., weight lifting, power lifting, and bodybuilding) develop pressure overloads due to the high systemic arterial pressure found in this type of exercise. It is hypothesized that chronically elevated aortic wall tension in strength-trained athletes is associated with aortic dilatation and regurgitation. The aim of this study was to evaluate aortic root size and the prevalence of aortic regurgitation in elite strength-trained athletes. The cohort included 100 male athletes (mean age 22.1 ± 3.6 years; all were finalists or medalists in the country) and 128 healthy age- and height-matched subjects (the control group). Aortic root diameters at end-diastole were measured at 4 locations: (1) the aortic annulus, (2) the sinuses of Valsalva, (3) the sinotubular junction, and (4) the maximal diameter of the proximal ascending aorta. Aortic root diameters at all levels were significantly greater in the strength-trained athletes (p <0.05 for all comparisons). When the strength-trained athletes were divided into quartiles of duration of high-intensity strength training (first quartile: <18 months; second quartile: >18 and <36 months; third quartile: >36 and <54 months; fourth quartile: >54 months), progressive enlargement was found at all aortic diameters. In conclusion, aortic root diameters in all segments of the aortic root were significantly greater in elite strength-trained athletes compared with an age- and height-matched population.